Cointegration and adjustment in the CVAR(É) representation of some partially observed CVAR(1) models - Søren Johansen (Econometrics, 2019)
A multivariate CVAR(1) model for some observed variables and some unobserved variables is analysed using its infinite order CVAR representation of the observations. Cointegration and adjustment coefficients in the infinite order CVAR are found as functions of the parameters in the CVAR(1) model. Conditions for weak exogeneity for the cointegrating vectors in the approximating finite order CVAR are derived. The results are illustrated by two simple examples of relevance for modelling causal graphs.
Keywords: C32; 330; adjustment coefficients; cointegrating coefficients; CVAR; causal models